2008
DOI: 10.1111/j.1742-481x.2008.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled 8‐week crossover clinical evaluation of the 3M™ Coban™ 2 Layer Compression System versus Profore™ to evaluate the product performance in patients with venous leg ulcers

Abstract: This study compared a two-layer (Coban 2 Layer) and a four-layer (Profore) compression bandage system in venous leg ulcer patients. Participants (n = 81) were enrolled into an 8-week, randomised, open-label, ten-centre, crossover clinical trial. The primary endpoint was bandage slippage measured at each dressing change. Secondary endpoints included wound healing, health-related quality of life (HRQoL) and patient preference. Mean slippage estimated from a mixed analysis of variance model (697 visits) was 2.48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
78
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 33 publications
1
78
0
3
Order By: Relevance
“…Our study found sub‐optimal health‐related quality of life, the CWIS global rating and satisfaction with this rating, 6 of 10 on average. This finding is not dissimilar to baseline scores reported in other research . Our sample reported higher scores for all sub‐scales of the CWIS than people who have gout‐related foot wounds and slightly higher physical symptom and daily living scores than people with lower leg ulcers .…”
Section: Discussionsupporting
confidence: 60%
“…Our study found sub‐optimal health‐related quality of life, the CWIS global rating and satisfaction with this rating, 6 of 10 on average. This finding is not dissimilar to baseline scores reported in other research . Our sample reported higher scores for all sub‐scales of the CWIS than people who have gout‐related foot wounds and slightly higher physical symptom and daily living scores than people with lower leg ulcers .…”
Section: Discussionsupporting
confidence: 60%
“…The study was not powered to detect differences in wound healing. 8 patients with ankle-brachial pressure indexes between 0.5 and 0.8. The product was safe and well tolerated, and results of laser Doppler flowmetry indicated significant improvements of the dermal capillary system After each application, a 10-cm long line was marked on the applied bandage.…”
Section: Peer-reviewed Datamentioning
confidence: 99%
“…Unter diesen Verbänden ist die Zeit bis zur Abheilung 30% kürzer als unter klassischen Kurzzugbandagen[14]. Während die ersten Vertreter dieser Ver bandsysteme aus Kurz und Langzugbin den bestanden, entfielen die Langzugbin den -ohne Wirksamkeitseinbußen -in den neueren Systemen[10].Ein gewisser Nachteil dieser Verbände ist, dass sie relativ dick auftragen und nor males Schuhwerk von dem Patienten oft nicht getragen werden kann. Diese Ver bände sollten daher vornehmlich in der Entstauungsphase Verwendung finden.…”
unclassified